2011
DOI: 10.1097/opx.0b013e3182045988
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Gap Detection for Pedestrians with Low Vision

Abstract: Purpose Pedestrians with low vision have identified crossing the street as a difficult task. With the increasing complexity of the crossing environment (actuated signals, roundabouts), the challenges are increasing. The purpose of this study was to evaluate the effect of two types of vision loss (central or peripheral) on the ability to detect gaps in traffic. Methods 41 subjects participated with 14 being fully sighted, 10 having central vision loss from age-related macular degeneration (AMD), and 17 having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 15 publications
2
29
0
Order By: Relevance
“…This conclusion also is supported by the results of Geruschat et al, who found that subjects with VA loss from age-related macular degeneration (AMD) performed similarly to normally sighted subjects in correctly identifying crossable and short gaps. 19 It also appears that the minimum VF size required to make accurate and reliable street crossing decisions lies between a 5.48 and 52.278 radius -the radii of the VF extents of the visually impaired subjects in the study of Cheong et al 4 and our studies, respectively. Further research is required to determine systematically how small the VF extent can be before a person no longer is able to detect crossable vehicular gaps accurately and reliably.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion also is supported by the results of Geruschat et al, who found that subjects with VA loss from age-related macular degeneration (AMD) performed similarly to normally sighted subjects in correctly identifying crossable and short gaps. 19 It also appears that the minimum VF size required to make accurate and reliable street crossing decisions lies between a 5.48 and 52.278 radius -the radii of the VF extents of the visually impaired subjects in the study of Cheong et al 4 and our studies, respectively. Further research is required to determine systematically how small the VF extent can be before a person no longer is able to detect crossable vehicular gaps accurately and reliably.…”
Section: Discussionmentioning
confidence: 99%
“…This result confirms the finding of Geruschat et al, who also found no significant difference in visually impaired subjects' traffic gap detection performance between the conditions of VþH and when hearing was occluded. 19 The nonlinear function describing the relationship between the street crossing decision variable and the vehicular gap time suggests that the decision variable is not discriminable across gap times below and above a certain value (gap time). All gap times below a certain value, quantified in our study as t min , will be classified by the subject as being ''insufficient time to cross.''…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of Geruschat et al 5 may be biased whereby the ability of the AMD subjects to identify accurately crossable and uncrossable gaps is inflated. This is because in their study there was an over-representation of short, uncrossable vehicular gap times assessed.…”
Section: Resultsmentioning
confidence: 96%
“…1 A key factor involved with making safe street-crossing decisions is vision. Previous street-crossing studies have shown that visually impaired and blind pedestrians, in comparison with normally-sighted pedestrians, make significantly more unsafe street-crossing decisions, 2,3 identify significantly fewer crossable gaps, [2][3][4] take significantly longer to identify a crossable gap, 2,[4][5][6] and have significantly reduced safety margins. 5 Collectively, the results of these earlier studies demonstrate that pedestrians with vision loss are potentially at risk when crossing the street in part because of their vision loss.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation